SISTEM INFORMASI PEMBAYARAN ANGSURAN PINJAMAN BERBASIS MULTI USER - Eny Endaryati; Muhammad Sidik (Pixel :Jurnal Ilmiah Komputer Grafis, 2018)
Banking institutions as one of the financial institutions have a strategic value in the economic life of a country. To achieve the goals that have been determined, the company will use the system that best suits the activities carried out by the company. The credit and installment system is a system that handles transactions related to providing credit to customers and at the same time paying credit installments. KSP Surya Melati is a savings and loan cooperative that collects funds from the community in the form of savings and deposits and distributes them back to the community in the form of lending. One of the activities carried out is the provision of credit to micro, small and medium entrepreneurs. KSP Surya Melati in calculating and managing its credit administration has used a computerized system. But the system still has shortcomings, namely when the credit installment payment transaction process, the determination of interest rates has not been computerized, in other words credit administration officers still input interest rates when the transaction takes place. This often results in errors in the calculation of interest installments that must be charged to customers. Therefore it is necessary to have a system that is used to store data changes in interest rates that occur in accordance with specified interest rates. Based on these problems, the compiler tries to provide a solution by making a Credit and Installment Management System using the Microsoft Visual Basic 6.0 programming language using the mysql server5 database which can be used as an improvement in the installment payment process, and can be used as a comparison material for the company without overriding the existing system walked all this time